Protein kinase C modulation of recombinant ATP-sensitive K(+) channels composed of Kir6.1 and/or Kir6.2 expressed with SUR2B - Thorneloe, Kevin S (Blackwell Science Inc, 2002)
The molecular identity of smooth muscle ATP-sensitive K(+) channels (K(ATP)) is not established with certainty. Patch clamp methods were employed to determine if recombinant K(ATP) channels composed of Kir6.1 and SUR2B subunits expressed by human embryonic kidney (HEK293) cells share an identical modulation by protein kinase C (PKC) with the vascular K(NDP) subtype of K(ATP) channel. The open probability of Kir6.1/SUR2B channels was determined before and after sequential exposure to pinacidil (50 μM) and the combination of pinacidil and phorbol 12,13-dibutyrate (PdBu; 50 nm). Treatment with PdBu caused a decline in channel activity, but this was not seen with an inactive phorbol ester, 4α-phorbol 12,13-didecanoate (PdDe; 50 nm). Angiotensin II (0.1 μM) induced a similar inhibition of Kir6.1/SUR2B channels in cells expressing angiotensin AT(1) receptors. The effects of PdBu and angiotensin II were blocked by the PKC inhibitor, chelerythrine (3 μM). Purified PKC inhibited Kir6.1/SUR2B activity (in 0.5 mm ATP/ 0.5 mm ADP), and the inhibition was blocked by a specific peptide inhibitor of PKC, PKC(19-31). In contrast, PdBu increased the activity of recombinant K(ATP) channels composed of Kir6.2 and SUR2B, or the combination of Kir6.1, Kir6.2 and SUR2B subunits. The results indicate that the modulation by PKC of Kir6.1/SUR2B, but not Kir6.2/SUR2B or Kir6.1-Kir6.2/SUR2B channel gating mimics that of native vascular K(NDP) channels. Physiological inhibition of vascular K(ATP) current by vasoconstrictors which utilize intracellular signalling cascades involving PKC is concluded to involve the modulation of K(NDP) channel complexes composed of four Kir6.1 and their associated SUR2B subunits.